Pembuatan Nugget Ikan sebagai Upaya Peningkatan Ekonomi Kreatif di Dusun Wainuru Kecamatan Salahutu Kabupaten Maluku Tengah Provinsi Maluku - Umi Kalsum Hehanussa; Tri Santi Kurnia (MANGENTE: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
Community service activities have taken place in Wainuru Hamlet, Salahutu District, Central Maluku Regency. The form of activity is training by making fish nuggets involving local housewives as an effort to increase the creative economy on a household scale. Fish nugget is a fish-based product that has been mixed with various spices, steamed and frozen as a ready-to-eat food that is modern, innovative, economical and has a high nutritional content and is very popular with children and adults. Apart from being known as a fish-producing area, Wainuru Hamlet is also known for its beautiful beach tourism. This is an opportunity for the residents of Wainuru Hamlet to introduce fish nuggets as a specialty of the area and can be a product to be marketed to visitors who come to visit Wainuru Beach.